Proceedings of the 3rd International Conference of Business, Accounting, and Economics, ICBAE 2022, 10-11 August 2022, Purwoker 2022
DOI: 10.4108/eai.10-8-2022.2320921
|View full text |Cite
|
Sign up to set email alerts
|

What About Transparency and Accountability in Charity Activist Community: A Study of Interpretive Netnography

Abstract: This research aims to understand the "depth" of reality and uncover the transparency and accountability behind the reality of the virtual community of charity. The reality of social media that is the subject of research is the Friday charity community. The research paradigm uses Interpretive with Netnographic analysis tools. This finding is that good deliberation and communication are manifestations of transparency, while accountability is based on awareness to place God as the highest stakeholder.The forms of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…However, the physical aspect has not been fully Credulous in the accountability of the LaaRiba community … Journal of Accounting and Investment, 2023 | 807 fulfilled because the financial records are only limited to cash in and out. Rayyani and Muchran (2022) researched charitable activist communities and found that accountability is based on awareness by placing Allah ‫)ﷻ(‬ as the highest stakeholder. Furthermore, Basri et al (2016) reported that in Islamic organizations both in Indonesia and Malaysia, a formal accountability mechanism is strongly encouraged, with financial reporting viewed as essential in enhancing accountability.…”
Section: Introductionmentioning
confidence: 99%
“…However, the physical aspect has not been fully Credulous in the accountability of the LaaRiba community … Journal of Accounting and Investment, 2023 | 807 fulfilled because the financial records are only limited to cash in and out. Rayyani and Muchran (2022) researched charitable activist communities and found that accountability is based on awareness by placing Allah ‫)ﷻ(‬ as the highest stakeholder. Furthermore, Basri et al (2016) reported that in Islamic organizations both in Indonesia and Malaysia, a formal accountability mechanism is strongly encouraged, with financial reporting viewed as essential in enhancing accountability.…”
Section: Introductionmentioning
confidence: 99%